A meta-analysis of residential PV adoption: the important role of perceived benefits, intentions and antecedents in solar energy acceptance. (February 2022) - Schulte, Emily; Scheller, Fabian; Sloot, Daniel; Bruckner, Thomas
Abstract: The adoption of residential photovoltaic systems (PV) is seen as an important part of the sustainable energy transition. To facilitate this process, it is crucial to identify the determinants of solar adoption. This paper follows a meta-analytical structural equation modeling approach, presenting a meta-analysis of studies on residential PV adoption intention, and assessing four behavioral models based on the theory of planned behavior to advance theory development. Of 653 initially identified studies, 110 remained for full-text screening. Only eight studies were sufficiently homogeneous, provided bivariate correlations, and could thus be integrated into the meta-analysis. The pooled correlations across primary studies revealed medium to large correlations between environmental concern, novelty seeking, perceived benefits, subjective norm and intention to adopt a residential PV system, whereas socio-demographic variables were uncorrelated with intention. Meta-analytical structural equation modeling revealed a model (N = 1, 714) in which adoption intention was predicted by benefits and perceived behavioral control (R 2 = .280), and benefits in turn could be explained by environmental concern, novelty seeking, and subjective norm (R 2 = .641). Our results imply that measures should primarily focus on enhancing the perception of benefits. Based on obstacles we encountered within the analysis, we suggest guidelines to facilitate the future aggregation of scientific evidence, such as the systematic inclusion of key variables and reporting of bivariate correlations. Highlights: Meta-analytical structural equation modeling (MASEM) approach. Heterogeneity among studies and inconsistent use of predictors hampers analysis. Perceived benefits are the strongest predictor of residential PV adoption intention. Benefits can be explained by environmental concern, novelty seeking and social norm. Consistent predictors and reporting standards mandatory for future meta-analyses.